Sorghum-soybean intercropping. XVI. Cutting systems, sowing date and cultivars of soybean in the forage production - Alcantara, Helio (2011)
This work aimed to evaluate the forage yield as a result of sowing dates, cultivars of soybean and cutting systems in a sorghum-soybean intercropping system. The experiments were carried out in Lavras-MG, in the agricultural years 2006/07 and 2007/08, in the Department of Agriculture of the UFLA. Were used a randomized complete blocks design in a 5 x 3 x 3 factorial scheme, being five sowing dates sorghum-soybean, three soybean cultivars and three cutting systems. Was used the sorghum monoculture, sown in five sowing dates, in order to compare it to the intercropping system. The sowing dates significantly changed the forage yield and crude protein content of the material intercropping, observing increasing returns to these characteristics with the early sowing. The soybean cultivars did not affect the forage yield of the intercropping. The cutting system 1 (near the soil surface) showed the highest yields of green mass, dry matter and crude protein of the material intercropping. The system of intercropping sorghum-soybean highest yield of green mass, dry matter and crude protein, compared to the monoculture of sorghum.